The missionary message of second Isaiah - Gelston, Anthony (Scottish journal of theology, 1965)
We have long been accustomed to thinking of the great prophet of the exile, whose words are recorded in Isa. 40–55, as the seer who first discerned plainly the truth that Yahweh is the only real God in existence, and who drew the inference that He must therefore be the God, not of Israel only, but of all men the world over. But we have not always borne in mind the way in which this revelation came to the prophet. This was no sudden disclosure, unrelated to Israel's previous experience of Yahweh; it was a revelation indeed, but it came to the prophet through the travail of his own and his people's experience in Babylon.